Multidisciplinary care of obese children and adolescents for one year reduces ectopic fat content in liver and skeletal muscle. Issue 1 (December 2015) - Fonvig, Cilius; Chabanova, Elizaveta; Ohrt, Johanne; Nielsen, Louise; Pedersen, Oluf; Hansen, Torben; Thomsen, Henrik; Holm, Jens-Christian
Abstract Background Ectopic fat deposition in liver and skeletal muscle tissue is related to cardiovascular disease risk and is a common metabolic complication in obese children. We evaluated the hypotheses of ectopic fat in these organs could be diminished following 1 year of multidisciplinary care specialized in childhood obesity, and whether this reduction would associate with changes in other markers of metabolic function. Methods This observational longitudinal study evaluated 40 overweight children and adolescents enrolled in a multidisciplinary treatment protocol at the Children's Obesity Clinic, Holbæk, Denmark. The participants were assessed by anthropometry, fasting blood samples (HbA1c, glucose, insulin, lipids, and biochemical variables of liver function), and liver and muscle fat content assessed by magnetic resonance spectroscopy at enrollment and following an average of 12.2 months of care. Univariate linear regression models adjusted for age, sex, treatment duration, baseline degree of obesity, and pubertal developmental stage were used for investigating possible associations. Results The standard deviation score (SDS) of baseline median body mass index (BMI) was 2.80 (range: 1.49–3.85) and the median age was 14 years (10–17). At the end of the observational period, the 40 children and adolescents (21 girls) significantly decreased their BMI SDS, liver fat, muscle fat, and visceral adipose tissue volume. The prevalence of hepatic steatosis changed from 28 to 20 % (p  = 0.26) and the prevalence of muscular steatosis decreased from 75 to 45 % (p  = 0.007). Changes in liver and muscle fat were independent of changes in BMI SDS, baseline degree of obesity, duration of treatment, age, sex, and pubertal developmental stage. Conclusions A 1-year multidisciplinary intervention program in the setting of a childhood obesity outpatient clinic confers a biologically important reduction in liver and muscle fat; metabolic improvements that are independent of the magnitude of concurrent weight loss. Trial registration ClinicalTrials.gov registration number:NCT00928473, the Danish Childhood Obesity Biobank. Registered June 25, 2009.